Effect on plant growth and heavy metal accumulation by sunflower - Chaves, Lucia Helena Garófalo; Estrela, Maria Alexandra; de Souza, Ramara Sena (Journal of Phytology, 2011)
The aim of this present study was to determine the effects of heavy metals (Cd, Cu and Zn) on plant growth, tissue concentration and examine their uptake by sunflower in soil. Three experiments (each corresponding to each metal) in a greenhouse were carried out in a complete randomized design, in each experiment, with five treatments and three replications, totaling 15 experimental units. Cadmium was applied at the rate of 0; 10; 20; 30 and 40 mg dm-3 of soil; copper and zinc levels were 0; 20; 40; 60 and 80 mg dm-3 of soil. Plant tops were harvested from 50 days after sowing. Cadmium and Zn both reduced the plant height of sunflower plant at higher concentration. The higher concentrations of Zn showed a significant decrease in leaf area. The heavy metals have no significant effect on plant dry matter but had significant effect on the accumulation of these elements in the plant parts, stem, leaves and roots.